Post-conflict tourist landscapes: between the heritage of conflict and the hybridization of tourism activity - Zeid A. Kassouha (Via@)
The upheavals caused by armed conflicts introduce profound changes in the tourism landscape. Physical, social or moral upheavals recompose the existing heritage and lead to its reinterpretation, they also create new heritage generated by the conflict itself. Post-conflict tourism is then in a situation of hybridization, between tourist practices detached from the events of the war (cultural tourism, seaside, etc.), and other practices that are intimately linked to these events (memory tourism, dark tourism, etc.).In this paper, we retrace the dynamics of this post-conflict "tourism resilience," through the observation of two examples in Bosnia and Herzegovina: the cities of Sarajevo and Mostar. We explore the urban and tourist landscape of these two cities in order to identify the different forms of tourism, memorialization or heritagization practices, related to the legacy of the Bosnian war (1992-1995).